Acoustic Measurement of Suspended Sediments in the Eastern Irish Sea - Rehman, Syed Shafiqur; Vincent, C.E. (Journal of Himalayan Earth Sciences, 1988)
An Acoustic Backscatter Meter of 2.7 MHz frequency and a working range of 64 cm has been used for measuring profiles of suspended sediments in the eastern Irish Sea. The ABM was running in burst mode, pinging at 4 Hz with a burst length of 160 seconds and a burst interval of 60 minutes. Data from the first two field deployments, each lasting up to 29 days, is presented here. The data suggests that most of the suspended load was fine silt/clay sized material showing strong modulation at the semi-diurnal and spring-neap tidal periods. Throughout the tidal cycle the concentrations remained very low except during flood currents of the spring tide when they reach up to 150 mg/l. A mild storm was also recorded during the first deployment which rested in high suspended load concentration rising up to about 50 cm above the seabed. Marked difference was also noticed between the suspended load concentration before and after the storm, suggesting that fine material had been advected out of the area by the storm. This is considered important in the dispersion of pollutants in shallow seas.